Ecosystems of Educational Disadvantage: Supporting Children and Young People receiving Child Protection and Welfare Services in Ireland - Flynn, Susan (My University, 2020)
Theoretically-informed focused commentary on the literature in this paper, considers the position of children and young people, as embedded within socio-ecological systems. The specific focus is on the educational disadvantage of children and young people susceptible to involvement from child protection and welfare services in the Republic of Ireland. To inform this, the utility of socio-ecological theory is emphasised, and from here, a Personal–Cultural–Structural (PCS) analysis is applied, to achieve an ecologically sensitive anti-discriminatory framework. Following a qualitative thematic review of literature, discussion addresses the question of what practitioners can do to promote the educational welfare of children and young people. The article is timely and necessary as existing evidence indicates that factors associated with educational disadvantage also increase susceptibility for involvement with child protection and welfare services. Yet, despite the compounded disadvantage this implies, little is understood about how these factors interact in practice. Overall, better understanding of educational underachievement is required, in the context of its negative and pervasive long-term effects, including decreased well-being, poorer health, and unemployment.
PUBLISHED
Keywords: Educational disadvantage; Child protection; Welfare; Education; Social work